Inadvertent Intrathecal Administration of Digoxin, with Review of the Literature - Burton J. Tabaac; Ian O. T. Laughrey; Hany F. Ghali (Case Reports in Neurological Medicine)
While the systemic effects of digoxin have been studied, limited data exist on the effects of neuraxial administration. Prior case reports document how digoxin and lidocaine share indistinguishable vials and were inadvertently stocked together in spinal and epidural anesthesia kits, necessitating a need for further implementation of safety measures. Here, we report the poor progression and brain death of a postpartum woman after accidental administration of intrathecal digoxin during a routine elective cesarean section (C-section). It is imperative that quality improvement and safety measures are taken to avoid the recurrence of this medical error.